In Vitro Regeneration of Aromatic Rice (Oryza Sativa L. Var. Doairgura) - Goswami, Barna; Banu, Tanjina Akhtar; Akter, Shahina; Afrin, Sadia; Habib , Ahashan; Khan, Salim (Bangladesh Journal of Botany, 2022)
Rice (Oryza sativa L.) is the world’s most important cereal crop. The Doairgura variety (O. sativa L.) is a low-yielding, high-quality aromatic rice-producing variety in Bangladesh. This study was undertaken to develop an in vitro regeneration protocol through in vitro callus induction. MS media supplemented with different concentrations of 2, 4- D (0.5, 1.0, 2.0 and 3.0 mg /l) were used for callus induction from the mature dehusked rice seeds. The best results for callus formation was obtained on MS media supplemented with 2.0 mg/l 2, 4-D. Shoot regeneration from in vitro cultured callus was tested with different combinations (BAP, NAA, Kn mg/l) of hormone containing MS media. The highest regeneration frequencies (100%) as well as the highest average shoot per culture (15.3) were recorded on the MS media supplemented with 2.0 mg/l BAP and 1.0 mg/l NAA. For root induction, hormone free MS media showed better results. After hardening, the plantlets were transferred to soil. This protocol is relatively simple and reproducible. Bangladesh J. Bot. 51(4): 677-682, 2022 (December)